Overall survival of pseudomyxoma peritonei and peritoneal mesothelioma patients after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy can be predicted by computed tomography quantified sarcopenia. Issue 11 (November 2018) - Galan, Alexandre; Rousset, Pascal; Mercier, Frederic; Képénékian, Vahan; Valette, Pierre-Jean; Glehen, Olivier; Passot, Guillaume
Abstract: Background: Malnutrition is associated with increased postoperative morbidity in abdominal surgery. This study aimed to determine if sarcopenia and/or abdominal fat composition could predict postoperative outcomes for patients undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) for pseudomyxoma peritonei (PMP) and peritoneal mesothelioma (PM). Methods: All patients who underwent a complete CRS-HIPEC for PMP and PM, between January 2009 and September 2017, were retrospectively studied. Preoperative computed tomography (CT) was used to measure the cross-sectional surface of skeletal muscle mass and adipose tissue (visceral and subcutaneous), at the level of the third lumbar vertebrae, to assess for sarcopenia and abdominal fat composition. Results: Among 115 patients, 82 were treated for PMP and 33 for PM. 64 patients (55.7%) were sarcopenic on the preoperative imagery. Major postoperative complications occurred in 63 patients (54.8%), without observable difference between sarcopenic and non-sarcopenic patients (56.2% vs. 52.9%; p = 0.723). The median overall survival (OS) was 73.3 for the patients with a normal muscle mass and 57.2 months for the sarcopenic patients (p = 0.05). Conclusion: CT measured sarcopenia is an independent predictive factor for overall survival in patients treated for PMP and PM with CRS-HIPEC, but cannot predict postoperative morbidity.